Parasites in Fresh Water Ornamental Fish (Cupang, Guppy and Rainbow Fish) - M. Alifuddin; Yani Hadiroseyani; I. Ohoiulun (Jurnal Akuakultur Indonesia)
Parasite inventory on some fresh water ornamental fish was done by survey methode. Parasites found from cupang fish namely Trichodinid (Ciliophora), Dactylogyrus sp. and Gyrodaclylus sp. (Platyhelminthes), Acanthocephala and cystic form; in guppy fish Trichodinid (Ciliophora), Gyrodaclylus sp. (Platyhelminthes) and Lerneae sp. (Crustasea); on rainbowg found Trichodinid (Ciliophora), Dactylogyrus sp., Gyrodaclylus sp. (Platyhelminthes), Acanthocephala, Lerneae sp. (Krustasea) and cystic form. Parasites found known as ecto, meso and endoparasites. From this study, there is correlation between parastes present with length fish.